Carceral logics: human incarceration and animal captivity - Gruen, Lori; Marceau, Justin (Cambridge University Press, 2022)
Paula Tarankow, "Race and the carceral logics in the history of the American Animal Welfare Movement" -- Richard Cupp, "Criminal Justice Reform and animal abuse : seeking an uneasy middle ground" -- Ashley Beck, "Giving a voice to the voiceless : combating animal cruelty in the courtroom" -- Pam Frasch, "Examining anti-cruelty enhancements - historical context and policy considerations" -- Benjamin Levin, "Carceral progressivism and animal victims" -- Jennifer Chacon, "Caging and immigration enforcement" -- Sam Kamin, "The failure of the war on drugs" -- Tammy Kuennen, "Lessons learned from the tough on crime approach to IPV" -- Aya Gruber, "Progressive pet issues and the carceral carve-out" -- Delci Winders, "Beyond codifying the contours of confinement" -- Justin Marceau, "Carceral logics beyond incarceration" -- Jessica Pierce & Marc Bekoff , "Give us our freedoms" -- Maneesha Deckha, "(Human) children and humane-washing in prisons, detention centres, and zoos and aquaria" -- Karen Morin, "Bovine lives & the making of a 19th c. American Carceral Archipelago" -- Kelly S. Montford, "The prison as multi-species carcerality" -- David Pellow, "Animal liberation prisoner and the repression of intersectional ecological justice movements" -- Vik Amar and Alan Chen, "Cause lawyering for the caged : a comparative examination of law reform approaches in the prisoners' rights and Animals Rights Movements" -- Jessica Eisen, "Habeas Corpus for non human animals : towards a critical approach" -- Doug Kysar, "False imprisonment" -- Will Potter, "Imagining animal protection as a Civil Rights Movement" -- Lori Gruen, "Abolition : thinking beyond carceral logics".